DO CORPORATE GOVERNANCE AND FINANCIAL CHARACTERISTICS MAY INCREASE CSR DISCLOSURES? - Maria Ariesta Utha; Abubakar Arif; Puspahadi Boenjamin (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
The purpose of this study was to analyze the effect of corporate governance and financial characteristics on the disclosure of Corporate Social Responsibility (CSR). The corporate governance variable uses the composition of the board and board committees, while the financial characteristics are proxied by the size of the company. The sampling technique used was purposive sampling. A total of 17 companies used in this study were selected with the provisions of being included in the SRIKEHATI Index ranking from 2016 to 2020 with a total data of 85 observations. The method of analysis uses multiple linear regression panel data. The results show that corporate governance as measured by the composition of the board has a positive and significant effect on CSR disclosure, while the board committee has no significant effect on CSR disclosure even though the resulting coefficient is positive. The financial characteristics that are proxied through the size of the company also do not have a significant effect on CSR disclosure. Meanwhile, of the many proxies of corporate governance and financial characteristics, only 2 corporate governance variables and 1 variable are used to measure financial characteristics. The contribution of this research is that good governance through the role of the composition of the board of commissioners can improve the quality of CSR disclosure, so companies need to improve the composition of the board of commissioners in the company.